Moving towards Understanding One An-Other: Cornelia Roux on Religion, Culture and Human Rights - Becker, A. (Journal for the study of religion, 2014)
Professor Roux is a pioneer in the field of interreligious, intercultural and human rights education. This article will focus on her contribution to understanding diversity in humankind and to enhancing inclusivity. An overview of her work demonstrates that she envisioned an understanding of diversity through education. She identified human rights values as common denominators within cultural and religious spaces of fear and resistance. She also focused on interreligious and intercultural dialogue in education as a means to enhance empathetic and caring interactions with others. In recent years, Roux has initiated three projects: The first was titled Understanding Human Rights through Different Belief Systems: Intercultural and Interreligious Dialogue (2005 - 2008). A follow-up project, Human Rights Education in Diversity: Empowering Girls in Rural and Metropolitan School Environments (2010-2013), focused on gender equity and social justice as priorities to facilitate an understanding of diversity (Roux 2012).An awareness of the importance of human rights literacy and human rights education in creating a sustainable environment for human rights and understanding within a multi-religious and multi-cultural society lead to the development of a third project titled Human Rights Literacy: A Quest for Meaning (Roux & Du Preez 2013). Drawing on Bauman’s (1994) conceptualisation of moral responsibility and relations of proximity anddistance, our article uses data from this latest project to demonstrate how human rights literacy could facilitate moving towards understanding one another. Qualitative comments from participants, which were probed during the focus group discussions, seem to indicate that freedom of choice and association are often used to mask exclusion and protect spaces of sameness and distance. Some students’ quest to move to understanding the other and in being responsible for the other, was illustrated by their description of the consequences of finding comfort in rights and the security of codes ofconduct.Keywords: human rights, diversity, difference, inclusivity, culture, religion, interreligious and intercultural dialogue, meaning, understanding, self and other